Islam and human psychology - Raheela Khalid Qureshi; Q. H. Aziz Ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Psychology plays a vital role in human personality. Islam itself is deeply interested in human psychology. The article discusses the connection of human psychology with Islam. When we discuss psychology, it comes the concept of spirit, self, heart and wisdom. Islam discusses these aspects of human personality and their role in life in Holy Quran. The article also reveals the opinion of different scholars, scientists and psychologists about faith and psychology. Islam lays stress on doing good deeds and avoiding of committing sins. The article also gives an idea how good deeds and attributes make an individual personality good or bad.
Keywords: 330